Model Rencana Pembelajaran Semester (RPS) Menggunakan Konsep Kurikulum Mandiri Pada Mobile Learning - Anugerah Bagus Wijaya; Irfan Santiko; Suliswaningsih Suliswaningsih; Aulia Hamdi; Luky Rafi Anuggilarso; Salsa Billa Zulmi Zettira (Fakultas Ilmu Komputer, Universitas Klabat, 2023)
The curriculum is a guide for all students and students in carrying out the learning process in schools and tertiary institutions. The discussion in this article discusses the curriculum at the tertiary level. The sub-discussion that will be studied is about the Rwncana Pembelajaran Semester (RPS). A tertiary institution certainly has guidelines in curriculum development. This curriculum will be reduced to a standard that influences the teaching and learning process. The problem that occurs is that it is often found that learning plans do not always go according to the guidelines they have. This causes the teaching and learning process to be not in line with the goals to be achieved at the end of the lesson. In this article, we will review how to conceptualize a learning plan with the currently popular model, namely mobile learning or abbreviated as m-learning. In m-learning there is a pattern that is considered in accordance with the 5.0 era of society approach, namely running independently. This solution was provided based on the survey method given to a number of respondents who considered that learning would be more effective if there was an independent curriculum that was easily developed and adapted to current learning conditions.